The outcome of hospital-acquired pneumonia in patients admitted for long-term care according to the antibiotic duration - Eman Shebl; Ahmed M Said; Lobna A El-Korashi; Hoda A Ibraheem (Egyptian Journal of Chest Disease and Tuberculosis, 2019)
Background Hospital-acquired pneumonia (HAP) is a leading cause of morbidity and mortality. The ideal duration of antibiotic therapy for HAP is unclear. Too short antibiotic course carries the risk of treatment failure, whereas unnecessary long antibiotic course may be associated with antibiotic resistance, antibiotic-related adverse effects, and more costs. The aim of this study was to evaluate the outcome of HAP in patients admitted for receiving long-term care according to the antibiotics duration. Patients and methods This study included 120 patients admitted for long-term care who developed HAP (59 males and 61 females) with age range from 18 to 92 years. The studied patients with HAP who received appropriate initial antibiotic therapy were classified into two groups: one group received short-course antibiotics (7–8 days), and the other group received long-course antibiotics (14–15 days). The outcome of HAP was evaluated and compared between both groups. Results The present study showed that in patients who received short course of antibiotics (7–8 days) compared with patients who received longer course of antibiotics (14–15 days), there was no significant difference in the 28-day mortality (22 vs. 19.7%, P=0.75) or in the recurrence rate (30.5 vs. 31.1%, P=0.94). Moreover, in this study, short-course antibiotics had a significantly higher 28-day antibiotic-free days (P<0.001) and significantly lower number of patients who developed drug-resistant microorganisms (P=0.04). Conclusion Short course of antibiotics for the treatment of patients with HAP, who had received appropriate initial empirical therapy, is not inferior to the longer course regarding the 28-day mortality rate and the risk of recurrence. Furthermore, short course of antibiotics was associated with increased 28-day antibiotic-free days and reduced the recurrence of pneumonia owing to resistant organisms.